2012
DOI: 10.4070/kcj.2012.42.9.641
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction in a Young Man; Fatal Blow of the Marijuana: A Case Report

Abstract: Marijuana is known to have been used for medicinal and recreational purposes for thousands of years. Although marijuana has some diverse effects on cardiovascular system, there is insufficient knowledge concerning acute myocardial infarction (AMI) associated with marijuana and its underlying mechanism. We report the case of a 26 year-old young man suffering from ST-elevated AMI caused by marijuana abuse, which was successfully treating with percutaneous coronary intervention. It should be kept in mind that mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Our study showed that AMI with marijuana group consisted more of younger, male (76.9% vs. 66.0%), African American (33.0% vs. 13.8%) patients compared to the non-marijuana group. The same result has been documented previously [ 2 , 9 ]. The higher weekend admissions in AMI-marijuana users could be related to recreational substance use more during weekends leading to higher AMI during the same time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that AMI with marijuana group consisted more of younger, male (76.9% vs. 66.0%), African American (33.0% vs. 13.8%) patients compared to the non-marijuana group. The same result has been documented previously [ 2 , 9 ]. The higher weekend admissions in AMI-marijuana users could be related to recreational substance use more during weekends leading to higher AMI during the same time.…”
Section: Discussionsupporting
confidence: 92%
“…The previous study has also shown that risk of AMI is amplified in the individuals who smoke marijuana [ 4 ]. There were 13 cases of chest pain and MI which were associated with marijuana smoking [ 9 ]. However, the previous studies had the small sample size and did not take the confounding factors into account in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Reported cardiovascular effects linked to cannabis include anecdotal cases of acute coronary syndrome, congestive heart failure, and arrhythmias (56, 97, 130, 133136). Patients with angina may have decreased time with chest pain onset due to the acute effects of cannabis use; also, myocardial infarction may be triggered by the acute effects of cannabis use (56).…”
Section: Medical Adverse Effectsmentioning
confidence: 99%
“…Additionally, review articles refer to the first hour after cannabis smoking as the riskiest hour, with the risk falling rapidly thereafter . Several authors have reported cases of CVD in proximity to cannabis use, sometimes supported by a positive urinalysis, as reported in Table . However, a positive cannabis finding is common up to 5 days after smoking and, in heavy smokers, positivity may be present for weeks or months .…”
Section: Introductionmentioning
confidence: 99%